Design and development of FOLLY: A self-foldable and self-deployable quadcopter - (:unkn) unknown (ELSEVIER FRANCE-EDITIONS SCIENTIFIQUES MEDICALES ELSEVIER, 2020)
New progress in the computational power of the flight controller industry drives quadcopters to be more preferable in various real-world applications. On the other hand, for different assignments, conventional quadcopter designs lack the ability to alter their configuration to satisfy the need to adapt to the requirements of the mission. In order to be entirely applicable to various kinds of assignments; being portable and transportable, having a low-volume is vital which is one of the main challenges in the design of quadcopters. This necessity, brings up a new research topic, namely morphologic quadcopters that are unique due to their nature of self-arm management feature. As morphologic quadcopters have self-arm management, they are capable of autonomously fold and deploy their arms which increases their functionally significantly. In this paper, we will present a self-foldable and self-deployable autonomous quadcopter, named as Folly. Folly is deployable to autonomous systems effortlessly as it is close-packed, mobile and has a self-arm management. In the design of self-arm management, we utilized a four-bar crank-rocker mechanism that is actuated by a single servo motor and coupled with spur gears that allow Folly to automatically fold and deploy its arms in a short period time, 0.6 s. The crank-rocker mechanism employed is scrutinized for position, velocity and acceleration kinematics to establish an efficient design. In addition, torque characteristics of the mechanism are analyzed numerically and collated with dynamic simulation to ensure desirable power transmission rates. Moreover, as a new approach, to deal with vibration effects in morphologic quadcopters, the frame material of Folly is selected to be acrylic. Furthermore, Folly has two flight modes which are the hover flight mode for horizontal flight patterns, and the object-tracking mode that enables indoor usage by preventing collision and increasing functionality. Various real-time experiments are performed to show the efficiency of the design of Folly. (C) 2020 Elsevier Masson SAS. All rights reserved.
Keywords: Quadcopter; Morphing; Design; Self-foldable; Self-deployable; Self-arm management; DRONE; UAV